Average Error: 0.0 → 0.0
Time: 13.9s
Precision: 64
$0.0 \le t \le 1$
${\left(1 - t\right)}^{3}$
$\sqrt[3]{{\left({\left(1 - t\right)}^{3}\right)}^{3}}$
{\left(1 - t\right)}^{3}
\sqrt[3]{{\left({\left(1 - t\right)}^{3}\right)}^{3}}
double f(double t) {
double r1977919 = 1.0;
double r1977920 = t;
double r1977921 = r1977919 - r1977920;
double r1977922 = 3.0;
double r1977923 = pow(r1977921, r1977922);
return r1977923;
}


double f(double t) {
double r1977924 = 1.0;
double r1977925 = t;
double r1977926 = r1977924 - r1977925;
double r1977927 = 3.0;
double r1977928 = pow(r1977926, r1977927);
double r1977929 = 3.0;
double r1977930 = pow(r1977928, r1977929);
double r1977931 = cbrt(r1977930);
return r1977931;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

${\left(1 - t\right)}^{3}$
2. Using strategy rm

$\leadsto \color{blue}{\sqrt[3]{\left({\left(1 - t\right)}^{3} \cdot {\left(1 - t\right)}^{3}\right) \cdot {\left(1 - t\right)}^{3}}}$
4. Simplified0.0

$\leadsto \sqrt[3]{\color{blue}{{\left({\left(1 - t\right)}^{3}\right)}^{3}}}$
5. Final simplification0.0

$\leadsto \sqrt[3]{{\left({\left(1 - t\right)}^{3}\right)}^{3}}$

# Reproduce

herbie shell --seed 1
(FPCore (t)
:name "pow(1-t,3)"
:precision binary64
:pre (<= 0.0 t 1)
(pow (- 1 t) 3))